(untitled) (Research, Society and Development, 2024)
Objective: To relate therapeutic advances in the sequelae of facial paralysis and their impact on self-image. Method: An integrative review of the literature was carried out, between the months of January and March of the year 2024, using the descriptors “Facial Paralysis”, “Treatment” and “Sequelae”, through the Scielo, MedLine, PubMed and Lilacs databases. Articles published in the last 5 years, in English, Portuguese and Spanish, were included, and theses, dissertations, letters to the editor and incomplete texts were excluded. Results and discussions: Patients with Bell’s Palsy are in extreme stress due to the sequelae of the condition. In 29% of patients, residual paresis appears with sequelae such as contracture in 17% and synkinesis in 16%. One of the effective and safe treatment options to mitigate the sequelae of facial paralysis is acupuncture, which can control the functional connection of the brain network and the functional activities of the cognitive area of ​​the brain. Furthermore, there are two rehabilitation techniques in the management of facial paralysis, facial mimicry and neuromuscular retraining, the application of botulinum toxin and mirror therapy. Conclusion: The sequelae of Facial Paralysis include several syndromes that occur after the acute condition of the pathology and have negative repercussions on the quality of life of patients, such as physical, social and psychological aspects. Even though several rehabilitation techniques are being developed for this purpose, it is important to highlight the need for more clinical studies to monitor therapy and results.